Compostos bioativos, atividade antioxidante e antiproliferativa de duas cultivares do café arábica (Coffea arabica L.) - Xavier, Mirieli Bernardes (2017)
Coffee is the second most consumed drink in the world and has Brazil as the main producer and exporter worldwide. Espírito Santo is the second largest producer of coffee in the country and much of its economy is focused on the trade of this fruit. The Arabica coffee (Coffea arabica L.) is the most valuable commercially and therefore is the most exported specie nowadays. In addition to its commercial value, coffee is also known to have pharmacological properties, which are reinforced by the presence of phytochemical constituents with antioxidant activity. Based on this, the present study evaluated the ethanolic extracts of two arabica coffee cultivars, "Catuaí vermelho IAC 99" and "Catucaí amarelo 2SL", in different post-harvest levels processing in order to quantify trigonelinne and chlorogenic acid by HPLC; verify the content of total tannins and flavonoids by colorimetric test; analyze the antiproliferative activity by the MTT method with healthy cells (human lymphocytes) and tumor cells (Sarcoma 180), and evaluate the antioxidant activity of the extracts through of four different colorimetric methods: ABTS·+ , DPPH, FRAP and Activity (Fe2+), in way to identify the extract with better performance, in order to guide the best condition for consumption and to demonstrate the possible influences of its processing on its phytochemical characteristics. The results suggest that the sample of “Catucaí amarelo seco e pilado” (CASP) had the best antioxidant activity among all the samples evaluated, but in general, the dry and pounded samples presented the best performance, implying that it is the best form of consumption, regarding the maximum use of its bioactive compounds. The class of compounds most correlated with the antioxidant activity was tannins, however, it is not possible to discard the action of the other compounds evaluated here. The roasting processes were detrimental to the quality of the drink, regarding the availability of bioactive compounds, the two roasting levels determined successive losses of bioactive compounds and, consequently, of the antioxidant activity. The MTT tests on healthy cells indicated that the samples served as mitogens, however, the sample “Catuaí vermelho cereja imaturo” (CVCI) obtained the highest percentage of proliferative activity, not being able to attest the accountable for this effect. In tumor cells, was noticed cell death in all conditions evaluated, where was found a correlation with the presence of chlorogenic acid and trigonelline, inferring that the presence of these compounds hinders cell death.